The dangerous book for boys / Conn Iggulden; Hal Iggulden - Iggulden, Conn
For every boy from eight to eighty, covers essential boyhood skills such as building tree houses, learning how to fish, finding true north, and even answering the age-old question of what the big deal with girls is. In this digital age there is still a place for knots, skimming stones and stories of incredible courage. This book recaptures Sunday afternoons, stimulates curiosity, and makes for great father-son activities. The brothers Conn and Hal have put together a collection of all things that make being young, or young at heart, fun--building go-carts and electromagnets, identifying insects and spiders, and flying the world's best paper airplanes.